DNA methylation: a cause and consequence of type 2 diabetes - Mirang Kim (Genomics & Informatics)
DNA methylation is a relatively stable epigenetic modification that can regulate and stabilize gene expression patterns and hence establish cell identity. Because metabolic intermediates are key factors of DNA methylation and demethylation, perturbations in metabolic homeostasis can trigger alterations in cell-specific patterns of DNA methylation and contribute to disease development, including type 2 diabetes (T2D). During the past decade, genome-wide DNA methylation studies of T2D have expanded our knowledge of the molecular mechanisms underlying T2D. This review summarizes case-control studies of the DNA methylome of T2D and discusses DNA methylation as both a cause and consequence of T2D. Therefore, DNA methylation has potential as a promising T2D biomarker that can be applied to the development of therapeutic strategies for T2D.